2016
DOI: 10.2196/resprot.6167
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Feasibility of Remote Patient Monitoring in Prenatal Care Using a Mobile App and Connected Devices: A Prospective Observational Trial

Abstract: BackgroundExcessive weight gain and elevated blood pressure are significant risk factors for adverse pregnancy outcomes such as gestational diabetes, premature birth, and preeclampsia. More effective strategies to facilitate adherence to gestational weight gain goals and monitor blood pressure may have a positive health benefit for pregnant women and their babies. The impact of utilizing a remote patient monitoring system to monitor blood pressure and weight gain as a component of prenatal care has not been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 9 publications
(4 reference statements)
4
76
0
5
Order By: Relevance
“…Although a multivariate analysis showed that these parameters did not influence our principal findings, smoking during pregnancy has adverse outcomes, although a reduced risk of developing of GHD in women who smoke has been demonstrated in many studies [4,9]. There is insufficient or conflicting evidence suggesting that immunological diseases influence the development of GHD [10][11][12][13]. The last limitation is that interference by family doctors or community midwives cannot be excluded.…”
Section: Strengths and Limitationsmentioning
confidence: 61%
See 1 more Smart Citation
“…Although a multivariate analysis showed that these parameters did not influence our principal findings, smoking during pregnancy has adverse outcomes, although a reduced risk of developing of GHD in women who smoke has been demonstrated in many studies [4,9]. There is insufficient or conflicting evidence suggesting that immunological diseases influence the development of GHD [10][11][12][13]. The last limitation is that interference by family doctors or community midwives cannot be excluded.…”
Section: Strengths and Limitationsmentioning
confidence: 61%
“…However, Marko et al (2016) reported a feasibility study of the use of a mobile phone app and connected digital devices (weight scale and blood-pressure monitor) for women at risk for adverse pregnancy outcomes. They concluded that this system is feasible for prenatal care [13]. Several studies of RM programs that assist nonpregnant patients with hypertension to control their blood pressure have been reported.…”
Section: Comparisons With Previous Trialsmentioning
confidence: 99%
“…Most recently, Minnesota, Washington, D.C., and Washington state piloted a promising intervention that couples virtual visits with in-person appointments. [56][57][58] Of note, none of these interventions focuses on the first prenatal care visit nor change the content of the first visit. Sentinel work on the establishment of prenatal care content and timing delineates the importance of developing a risk-responsive approach to prenatal care for women at risk (i.e., underserved, substance addiction, abuse-related issues, adolescents); their report underscored the importance of early care initiation to identify patient needs and perform interventions that may improve outcomes and increase compliance.…”
Section: Implications For Practice And/or Policymentioning
confidence: 99%
“…30 Compared with a laboratory setting, remote, real-time data collection using EMA reduces recall bias, is reliable, has ecological validity, and provides opportunities for more data points. 30,31 Data collection with EMA is feasible in diverse populations, including pregnant populations, [32][33][34][35][36][37][38][39][40] and has high participant satisfaction and completion rates up to 89%. 32,41,42 Given that many people carry their smartphones with them, participants can regularly complete short EMA surveys in their natural setting, limiting the reliance on in-person visits for data collection.…”
Section: Introductionmentioning
confidence: 99%